Metabolic activity of hydro-carbon-oxo-borate on a multispecies subgingival periodontal biofilm: a short communication - Shibli, Jamil Awad; Rocha, Thayane Furtado; Coelho, Fernanda [UNESP]; de Oliveira Capote, Ticiana Sidorenko [UNESP]; Saska, Sybele; Melo, Marcelo A.; Pingueiro, João Marcos Spessoto; de Faveri, Marcelo; Bueno-Silva, Bruno (Springer Nature, 2021)
Objective: This study evaluated the metabolic activity of hydro-carbon-oxo-borate complex (HCOBc) on a multispecies subgingival biofilm as well as its effects on cytotoxicity. Materials and methods: The subgingival biofilm with 32 species related to periodontitis was formed in the Calgary Biofilm Device (CBD) for 7 days. Two different therapeutic schemes were adopted: (1) treatment with HCOBc, 0.12% chlorhexidine (CHX), and negative control group (without treatment) from day 3 until day 6, two times a day for 1 min each time, totaling 8 treatments and (2) a 24-h treatment on a biofilm grown for 6 days. After 7 days of formation, biofilm metabolic activity was determined by colorimetry assay, and bacterial counts and proportions of complexes were determined by DNA-DNA hybridization. Both substances’ cytotoxicity was evaluated by cell viability (XTT assay) and clonogenic survival assay on ovary epithelial CHO-K1 cells and an osteoblast precursor from calvaria MC3T3-E1 cells. Results: The first treatment scheme resulted in a significant reduction in biofilm’s metabolic activity by means of 77% by HCOBc and CHX treatments versus negative control. The total count of 11 and 25 species were decreased by treatment with hydro-carbon-oxo-borate complex and CHX, respectively, compared with the group without treatment (p < 0.05), highlighting a reduction in the levels of Porphyromonas gingivalis, Tannerella forsythia, Prevotella intermedia, and Fusobacterium periodontium. CHX significantly reduced the count of 10 microorganisms compared to the group treated with HCOBc (p < 0.05). HCOBc and CHX significantly decreased the pathogenic red-complex proportion compared with control-treated biofilm, and HCOBc had even a more significant effect on the red complex than CHX had (p ≤ 0.05). For the second treatment scheme, HCOBc complex and CHX significantly decreased 61 and 72% of control biofilms’ metabolic activity and the counts of 27 and 26 species, respectively. HCOBc complex did not significantly affect the proportions of formed biofilms, while CHX significantly reduced red, orange, and yellow complexes. Both substances exhibited similar cytotoxicity results. Conclusions: This short communication suggested that the HCOBc complex reduced a smaller number of bacterial species when compared to chlorhexidine during subgingival biofilm formation, but it was better than chlorhexidine in reducing red-complex bacterial proportions. Although HCOBc reduced the mature 6-day-old subgingival multispecies biofilms, it did not modify bacterial complexes’ ratios as chlorhexidine did on the biofilms mentioned above. Future in vivo studies are needed to validate these results. Clinical relevance: HCOBc complex could be used to reduce red-complex periodontal bacterial proportions.
Keywords: Hydro-carbon-oxo-borate; Metaboloci activity; Peri-implantitis; Periodontal biofilm; Periodontal pathogens; Periodontitis